Security Protocols XVI 16th International Workshop, Cambridge, UK, April 16-18, 2008. Revised Selected Papers - Christianson, Bruce; Malcolm, James A.; Matyas, Vashek; Roe, Michael (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-proceedings of the 16th International Workshop on Security Protocols, SP 2008, held in Cambridge, UK, in April 2008. The 17 revised full papers presented together with edited transcriptions of some of the discussions following the presentations have gone through multiple rounds of reviewing, revision, and selection. The theme of this workshop was Remodelling the Attacker with the intention to tell the students at the start of a security course that it is very important to model the attacker, but like most advice to the young, this is an oversimplification. Shouldn't the attackers capability be an output of the design process as well as an input. The papers and discussions in this volume examine the theme from the standpoint of various different applications and adversaries.